Paint Desirable Subjects with Interactive Video Feedback - Ruimin Lyu; Haotian Wu; Zhongliang Yang (2013 International Conference on Computer-Aided Design and Computer Graphics, 2013)
In this paper we describe the creation and the presentation of interactive fractal paintings with paint systems based on VF(Video Feedback). VF occurs when a camera points to its own display. VF is able to generate evolving fractal patterns. But it is difficult to create artworks under specified subjects based on VF. To solve this difficulty, we implemented video feedback paint system by minimally modifying the bare-bones VF system. The system enables the user to draw shapes directly on a display engaged in VF. These shapes geometrically confine the VF dynamics and compose a designed 2D composition which can include specific subject matter. Artworks created using the system can generate evolving patterns with the viewer manipulating anything possible between the camera and the display yet always conform to designed 2D compositions.